Methods for fashion terms formation of the women's wardrobe in the English Language (on basis of the novel The Devil Wears Prada by L. Weisberger) - V V Vorobiev; G M Polyakova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2012)
The article is dedicated to the analysis of the methods for fashion terms formation of the women's wardrobe in the English Language. 37 fashion terms have been singled out from the novel The Devil Wears Prada by L. Weisberger and were analysed according to 3 methods of terms formation: morphological, morphologo-syntactical and syntactical.